Expolios de la mujer y el entorno en Gení y el Zepelín de José Luis Ramos Escobar - Morell, Hortensia R. (Latin American Theatre Review, 2013)
This essay explores the intertextual relations between the Puerto Rican writer’s one-act play Gení y el Zepelín and Chico Buarque de Hollanda’s Ópera do Malandro. This process uncovers not only Ramos’s borrowing of a Buarque ballad for his title, his protagonist, and his plot, but also the way he shares Brecht’s theatre poetics with his Brazilian counterpart. The study also reveals a complex textual web that includes Brecht’s Die Dreigroschenoper, Maupassant’s “Boule de Suif,” Queiroz’s “Tangerine Girl,” and García Márquez’s El otoño del patriarca. The interrelated works’ shared theme of the despoiling of women and the environment is analyzed through the lens of Gayle Rubin’s “The Traffic in Women.”